2015
DOI: 10.1002/qj.2580
|View full text |Cite
|
Sign up to set email alerts
|

The onset of the barotropic sudden warming in a global model

Abstract: The barotropic, vortex-splitting sudden warming is analyzed in a simple global model, comprising the rotating shallow-water equations on the sphere with and without the effects of thermal forcing. A quasi-stationary approach is suggested as an effective means of exploring the two-dimensional parameter space of forcing amplitude and a suitable measure of vortex strength. We find that the main dynamical regimes obtained previously in a quasi-geostrophic f -plane model by Matthewman and Esler persist in the globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…They concluded that no persistent vacillations exist in shallow water, again due in part to the build‐up of tropical easterlies, and that the vacillations obtained by Rong and Waugh were essentially a remnant of initial transience of the integrations resulting from the non‐zero initial conditions and relatively rapid initial growth of the topographic forcing. More recently, analysis of the barotropic sudden warming in a global shallow‐water model (Liu and Scott, ) hinted at the existence of vacillation regimes in a quasi‐stationary context, although integrations of that model over longer times again suffered the effects of unconstrained growth of equatorial easterlies present in Rong and Waugh.…”
Section: Introductionsupporting
confidence: 58%
“…They concluded that no persistent vacillations exist in shallow water, again due in part to the build‐up of tropical easterlies, and that the vacillations obtained by Rong and Waugh were essentially a remnant of initial transience of the integrations resulting from the non‐zero initial conditions and relatively rapid initial growth of the topographic forcing. More recently, analysis of the barotropic sudden warming in a global shallow‐water model (Liu and Scott, ) hinted at the existence of vacillation regimes in a quasi‐stationary context, although integrations of that model over longer times again suffered the effects of unconstrained growth of equatorial easterlies present in Rong and Waugh.…”
Section: Introductionsupporting
confidence: 58%
“…This system, which has been widely used in studies of Earth's stratospheric polar vortex (e.g., Juckes 1989;Norton 1994;Rong and Waugh 2004;Liu and Scott 2015;Scott 2016), allows us to isolate the dynamics associated with barotropic instability from those due to vertically propagating waves. In vorticity-divergence form, these equations are…”
Section: Model and Experimental Design A Shallow-water Modelmentioning
confidence: 99%
“…, which is the relevant vertical structure of the barotropic mode in a compressible atmosphere (Liu and Scott 2015). Here k 5 1 /4 (the appropriate value for a triatomic gas such as CO 2 , which is the major constituent of the Martian atmosphere), f 5 2V sinf, N 5 0.01 s 21 is the Brunt-Väisälä frequency, and D 5 11 km is the density scale height (approximate values taken from http://nssdc.gsfc.nasa.gov/planetary/ factsheet/marsfact.html).…”
Section: Model and Experimental Design A Shallow-water Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitchell et al () used extreme value theory and 2‐D moment diagnostics to characterize Arctic and Antarctic polar vortices and showed that moment diagnostics were a useful measure of vortex variability and could be used to help distinguish vortex‐split/displacement SSWs. Many studies of the polar vortex, stratospheric variability, and their connections have since made extensive use of geometric and moment diagnostics for studies based on modeling (e.g., Liu and Scott, ; Matthewman & Esler, ), reanalyses (e.g., Hannachi et al, ; Mitchell et al, ; Seviour et al, ), and climate model data (e.g., Maycock & Hitchcock, ; Seviour et al, ; Zhang et al, )…”
Section: Introductionmentioning
confidence: 99%